Factors Associated with Colorectal Cancer Diagnosis among Patients with Digestive Malignancies at the National Cancer Control Center of Niamey, Niger (2018–2023) - Amghar, Fatima Mohamed; Barikissou, Damien Georgia; Salifou, Alkassoum Ibrahim; Soumaila, Amadou; Aguemon, Badirou (European Scientific Journal, ESJ, 2026)
Introduction: Colorectal cancer (CRC) is a major public health concern, with a rising incidence in low- and middle-income countries, particularly in sub-Saharan Africa. In Niger, data on factors associated with CRC are limited. This study aimed to identify sociodemographic, socioeconomic, clinical, and behavioral factors associated with the diagnosis of colorectal cancer among patients with digestive cancers. Methods: This retrospective analytical study was conducted at the National Cancer Control Center (CNLC) of Niamey, including patients with histologically confirmed digestive cancers between January 1, 2018, and December 31, 2023. Associations between CRC diagnosis and independent variables were assessed using bivariate analyses (χ² or Fisher’s exact test), followed by multivariate logistic regression for variables with p < 0.20. Adjusted odds ratios (ORs) with 95 % confidence intervals (CI) were calculated. Results: Among 424 digestive cancer cases, 231 (54.5 %) were colorectal cancers. After excluding incomplete records, 222 patients were analyzed. The mean age was 48.6 ± 15.4 years, with a male predominance (62.2 %). In multivariate analysis, no income was significantly associated with CRC diagnosis (OR = 4.85; 95 % CI: 1.40–16.00; p = 0.014). A consultation delay of two years or more was also significantly associated with CRC diagnosis (OR = 4.05; 95 % CI: 0.90–18.00; p = 0.034). Behavioral factors (tobacco, alcohol, obesity) and family history were not significantly associated with CRC. Conclusion: This study highlights that low socioeconomic status and delayed consultation are strongly linked to the hospital diagnosis of colorectal cancer in Niger. Strengthening early detection, community awareness, and financial access to care is essential to improving patient management and prognosis.